ANALYSIS OF ASPECTS OF PRODUCT’S QUALITY TO INCREASE CONSUMER’S PURCHASE INTENTION ON SNEAKER - Kartini, Tini; Putranto, Nur Arief Rahmatsyah (Journal of Business and Management, 2017)
Abstract. The development of an increasingly advanced globalization era and highly dynamic product marketing conditions make market actors and producers must be ready to be in a tight competition. The competition also occurs in the domestic shoes industry that should not only compete with the local products but also the foreign products. However, in the competition, consumers prefer to buy foreign sneaker than local sneaker, because of the assumption of better product’s quality. Researcher is interested in analyzing the quality of the product because the quality of the product is one factor that has an influence on purchase intention. This research aims to increase the consumer’s purchase intention, so that it is expected to increase the purchase of local sneaker products by testing some hypotheses about whether there is positive relation and significant relation between performance, reliability, conformance, durability, features, aesthetics and serviceability with purchase intention. The analysis technique used in this research is Pearson Product Moment Correlation and Multiple Linear Analysis with 384 respondents. The results of this research indicate that performance, features, reliability, conformance, durability, serviceability, and aesthetics have positive relation and significant relation to purchase intention. However, the aspects of aesthetics and durability are the aspects that have the most influence on purchase intention. This research recommends local sneaker producers to improve the aesthetics and durability aspects by conducting market survey related to consumer tastes in aesthetics aspects, replacing used shoes materials with stronger materials, using additional certain materials, and replacing upper shoes materials with the more durable material. Keywords: Purchase Intention, Product's Quality, Performance, Features, Reliability, Conformance, Durability, Serviceability, Aesthetics.